2017
DOI: 10.1007/978-3-319-68705-6_13
|View full text |Cite
|
Sign up to set email alerts
|

On H-Topological Intersection Graphs

Abstract: Biró, Hujter, and Tuza (1992) introduced the concept of H-graphs, intersection graphs of connected subregions of a graph H thought of as a one-dimensional topological space. They are related to and generalize many important classes of geometric intersection graphs, e.g., interval graphs, circular-arc graphs, split graphs, and chordal graphs. Our paper starts a new line of research in the area of geometric intersection graphs by studying H-graphs from the point of view of computational problems that are fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…On the positive side, we show that when H is a tree, then Minimum Dominating Set is FPT parameterized by the size of H. This significantly extends the result from [CTVZ17] for stars to arbitrary trees. We actually prove a slightly more general result, namely that Minimum Dominating Set is FPT on chordal graphs G parameterized by the leafage of the graph, i.e.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…On the positive side, we show that when H is a tree, then Minimum Dominating Set is FPT parameterized by the size of H. This significantly extends the result from [CTVZ17] for stars to arbitrary trees. We actually prove a slightly more general result, namely that Minimum Dominating Set is FPT on chordal graphs G parameterized by the leafage of the graph, i.e.…”
Section: Introductionsupporting
confidence: 69%
“…The first steps in this direction were done by Chaplick et al in [CTVZ17] who showed that Minimum Dominating Set is fixed-parameter tractable (FPT) on K 1,d -graphs parameterized by d. In this paper we show that Minimum Dominating Set is W[1]-hard parameterized by H and the size of the solution. Thus the existence of an FPT algorithm for a general graph H is very unlikely.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We obtain new algorithmic results on clique, coloring, and isomorphism problem. In a companion paper [7], we studied recognition and dominating set problems on H-graphs. We begin with related graph classes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an alternative view of host domains has been considered quite recently through the notion of H-graphs [3,5,6,12], i.e., for a fixed graph H, a graph G is an H-graph when it is an intersection graph of connected subgraphs of a subdivision of H. Here, interval graphs are the K 2 -graphs and circular arc graphs are the K 3 -graphs. While there is a natural notion of proper H-graphs [3] and these do indeed restrict H-graphs (for every H), we believe that the more restrictive non-crossing H-graphs might have a nicer structure and lead to easier (and more efficient) algorithms.…”
Section: Discussionmentioning
confidence: 99%